OPTIMASI ZONASI PADA TAMAN NASIONAL LAUT KEPULAUAN SERIBU - , BETTY RAHMA HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Zoning arrangement is an attempt to optimize the space allocation functions and potentials of natural resources and ecosystems on any part of the Kepulauan Seribu National Park (TNKpS) region, and the implementation and enforcement of the legal provisions on sanctions violations carried out in each area zone of TNKpS. A study of the current zoning applied in TNKpS indicates that the current zoning system is not effective in the areas management. This study aims to determine the optimal allocation of broad zones in bridging the various interests in the management of TNKpS. The method of analysis used spatial analysis using Geographic Information Systems (GIS) and socio-economic analysis, later in the formulation of optimal allocation of zoning uses quantitative analysis âMulti Objective Goal Programmingâ. The results showed that the combination of broad zones of optimal allocation in TNKpS analysis using the Multi Objective Goal Programming